2011
DOI: 10.1128/iai.00985-10
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Host Genetic Background and Mycobacterial Pathogen on Susceptibility to Infection

Abstract: The present study examined the differential contribution of host genetic background and mycobacterial pathogen variability to biological and mechanistic phenotypes of infection. For this purpose, A/J and C57BL/6J mice were infected intravenously with a low dose of Mycobacterium tuberculosis H37Rv or the Russia, Japan, and Pasteur substrains of Mycobacterium bovis bacille Calmette-Guérin (BCG). The pulmonary bacterial counts (number of CFU) and transcript levels of select cytokines (e.g., Ifng, Il12b, and Il4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…The relatively high number of SNPs we identified in all isolates could be partially caused by natural variation, as we included all genes from 7 strains isolated from patients diversely located. Selective diversification of M. tuberculosis isolates might also explain an association between host response and strain genetic background as previously reported [12, 13]. Several lines of evidence in this study support a significant role of natural selection in shaping M. tuberculosis genomes.…”
Section: Discussionsupporting
confidence: 86%
“…The relatively high number of SNPs we identified in all isolates could be partially caused by natural variation, as we included all genes from 7 strains isolated from patients diversely located. Selective diversification of M. tuberculosis isolates might also explain an association between host response and strain genetic background as previously reported [12, 13]. Several lines of evidence in this study support a significant role of natural selection in shaping M. tuberculosis genomes.…”
Section: Discussionsupporting
confidence: 86%
“…First, the SNP distribution in genomes is not random, suggesting that diversifying selection is at work notably in genes playing a role in cell wall/membrane/envelope biogenesis, which tend to accumulate an excess of SNPs. This result is probably related to the lifestyle of the tubercle bacilli, producing long chronic colonization of hosts, which might result in selection pressure for arms races with the host, e.g., to evade host defenses (Dawkins and Krebs 1979) or diversifying selection to adapt to different host genetic backgrounds (Di Pietrantonio et al 2011). While we still lack examples of horizontal gene transfer after the last common ancestor of MTBC, our approach was not aimed at identifying regions that could not be mapped in extant genomes; rather, we showed that regions transferred to the ancestor of MTBC also accumulate an excess of SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…tuberculosis isolates found in epidemiologically defined clusters are defined as successful because they transmit and cause TB in more human hosts, in the same population, than the case for other isolates. It is also a generally accepted idea that overall strain success depends on a combination of strain virulence traits and host genetic factors (8,14,16,62,63). The contribution of mycobacterial VFs to establishing disease (TB) or causing pathogenicity, however, was recently reemphasized (42,64); as VFs are likely to be lineage specific (23-25, 38, 43), their existence might have far-reaching impacts on the efficacy of new TB vaccines or drugs (65).…”
Section: Discussionmentioning
confidence: 99%